2008
DOI: 10.1016/j.febslet.2008.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of mutant PPARγ LBD complexed with 15d‐PGJ2: Novel modulation mechanism of PPARγ/RXRα function by covalently bound ligands

Abstract: Edited by Hans EklundKeywords: PPARc covalently bound ligand PPARc/RXRa activating process modulation mechanism Crystal structure a b s t r a c t 15-deoxy-D12,14 -prostaglandin J 2 (15d-PGJ 2 ) activates a nuclear receptor heterodimer, peroxisome proliferators-activated receptor c (PPARc)/ retinoid X receptor (RXRa) through covalent binding to Cys285 in PPARc ligand-binding domain (LBD). Here, we present the 1.9 Å crystal structure of C285S mutant LBD complexed with 15d-PGJ 2 , corresponding to the non-covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Subsequent studies using crystallography 28 or competitive ligand-binding assays revealed that these synthetic ligands and others bind to the canonical LBP of PPARγ; a variable-sized pocket within the interior of LBD conserved across the NR superfamily. Around the same time, the first identification of endogenous PPARγ ligands were made 29,30 , and more recent studies have revealed that endogenous ligands and synthetic ligands have overlapping binding sites in the PPARγ canonical LBP 24,26,31-33 . Thus, synthetic ligands are presumed to bind to PPARγ by competing with endogenous ligands for the same binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies using crystallography 28 or competitive ligand-binding assays revealed that these synthetic ligands and others bind to the canonical LBP of PPARγ; a variable-sized pocket within the interior of LBD conserved across the NR superfamily. Around the same time, the first identification of endogenous PPARγ ligands were made 29,30 , and more recent studies have revealed that endogenous ligands and synthetic ligands have overlapping binding sites in the PPARγ canonical LBP 24,26,31-33 . Thus, synthetic ligands are presumed to bind to PPARγ by competing with endogenous ligands for the same binding site.…”
Section: Discussionmentioning
confidence: 99%
“…In the molecular docking experiment, MH was predicted to bind at the identical ligand binding site as other PPARg agonists, such as 15-deoxy-PGJ2 (Waku et al, 2009) and the fatty acid ligand LNO2 (Cheng et al, 2009 Figure 1D). One hydrogen bond was observed between the hydroxyl group of the MH and the hydroxyl side chain of Ser 289 in PPARg ( Figure 1E).…”
Section: Mh Increased the Expression Transcription And Dna Binding Amentioning
confidence: 99%
“…Oxidized unsaturated fatty acids effectively stabilize the Ω-loop region through formation of a covalent bond with Cys285 (16). Morikawa and colleagues proposed a model involving conformational changes of the PPARγ LBD during activation by 15-deoxy-∆ 12,14 -prostaglandin J 2 (15d-PGJ 2 ), where covalent modification of Cys285 may act as a "switch" for activation.The non-covalently bound, inactive intermediate complex is designated as the "docked state" and the covalently bound, active complex as the "locked state"(32). The transcriptional activity of endogenous unsaturated fatty acids is specific for ligand type.For example, 15-oxo-eicosatetraenoic acid (15-oxo-ETE) and 15d-PGJ 2 activate PPARγ transcription while 8-oxo-ETE does not, though all three can form a covalent linkage with Cys285 through an α,β-unsaturated ketone(33).…”
mentioning
confidence: 99%